Peran Pengawas Dalam Implementasi Kurikulum Merdeka (IKM) Di MI Wilayah Kalidawir Tulungagung - Asrori Mustofa (Simpati, 2024)
The aim of this research is to analyze the role of supervisors in the implementation of the independent curriculum (IKM) at MI Kalidawir Tulungagung Region. The research method used is a qualitative research approach. Data collection techniques are used to explore data by conducting interviews, observations, interviews and documentation. The results of his research urge supervisors to implement the independence criteria, namely that supervisors have a very important role in madrasa training and development. The monitoring mechanism carried out by supervisors in implementing the independent curriculum consists of three stages, namely planning, implementation, evaluation and follow-up. The supervisor's role in implementing the independent curriculum consists of academic supervision, managerial supervision, and research and development supervision. In the aspect of academic supervision, supervisors guide and develop teachers to make learning plans based on the characteristics of the independent curriculum. In the managerial aspect, supervisors and coaching madrasa heads in creating KOM and other madrasa programs in preparing independent synchronization. Meanwhile, in the aspect of research and development supervision, supervisors motivate madrasa heads and teachers to carry out and create best practices related to the implementation of the independent curriculum.